Roberto Arlt y el campo intelectual argentino de los años veinte y treinta - Letourneur, Marina (Diálogos Latinoamericanos, 2013)
Taking as a basis Beatriz Sarlo and Carlos Altamirano's analysis of the intellectual field (Literature and Society), inspired by Bourdieu's work on the literary field, we are going to study the Argentinian intellectual field of the 1920s and the 1930s as well as the influence that Roberto Arlt had (or didn't have) in this intellectual field. The writer's short but prolific career —nowadays regarded as one of the greatest authors in the first half of the century— is, as a matter of fact, marked by his stormy relationship with most of the intellectual field in his days. When his misused Spanish and his use of lunfardo (slung of the slums of Buenos Aires) were censured, he, the son of immigrants, claimed his difference and vehemently criticized the ‘recognized’ authors, those who showered praise upon them and those who despised him.